Subjektivitas Najib Kailani dalam Cerpen Udara yang Dingin - Andika, Kenny (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
The short story Udara yang Dingin is Najib Kailani's criticism of the patriarchal culture that positions women under the control of men. This research discusses the subjectivity of characters and authors within the scope of the short story Udara yang Dingin by Najib Kailani using Slavoj Zizek's theory of Subjectivity. Zizek's view is that humans can achieve their freedom and purity by letting go of the entangling symbolic towards the wholeness that is longed for in the real. Conversely, humans will be in a symbolic trap as long as they allow themselves to be trapped in the circle of ideological false consciousness. This research shows that there is a radical effort made by Fatimah's character to release herself from the symbolic by breaking the normative rules that surround her. However, the radical action taken by Fatimah in this short story is not carried out by Najib Kailani, who is only immersed in ideological fantasies.